Forecasting in Crisis Management Organization - V. N. Lokhanova (Управление)
The relevance of scientific research in the field of crisis management due to the depressed state of the Russian economy, including its business sector. One of the important directions of the scientific school of the Department of corporate management is forecasting the development of the organization in crisis. The article defines the essence of anti-crisis forecasting, its objective, stages and influencing factors. Special attention is given to forecasting methods, their classification, selection criteria. The contribution of famous Russian and foreign scientists to the theory of forecasting of bankruptcy of the organization, a comparative analysis of the advantages and disadvantages of different methods of forecasting. The list of critical indicators of the probability of bankruptcy.